My first book of sign - Baker, Pamela J., 1947- (Kendall Green Publications, 1986)
Pictures of children demonstrate the forming in sign language of 150 basic alphabetically arranged words, accompanied by illustrations of the words themselves. Includes a discussion of fingerspelling and general rules for signing.